EKSPLORASI KREATIVITAS SENI BUDAYA PESERTA DIDIK MELALUI PEMBELAJARAN TARI DAN MUSIK PUTRI TANGGUK DI SEKOLAH DASAR - Febrian; Ryan Jahyus, Muhammad; Arabi , M. Akram; Hariska, Agung; Saputra, Deka; Dzulqadri , Abraar; Yoga Septian , Fikra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to explore learners' creativity through learning the dance and music of Putri Tangguk in primary school. This cultural arts learning is designed to introduce students to traditional arts, particularly regional dance and music, and to develop their creativity in the arts. The research method used was descriptive qualitative with observation, interview, and documentation as data collection techniques. The results showed that Putri Tangguk dance and music learning can increase students' involvement in the learning process and hone their creativity skills. Students are allowed to improvise in dance and musical movements, which will enable them to express their creative ideas. In addition, this learning also plays a role in preserving local culture and introducing traditional values to the younger generation. Nonetheless, its implementation has some constraints, such as limited musical instruments and learning time, which require practical solutions to optimize learning. Overall, this research indicates that Putri Tangguk dance and music learning is an effective method in developing students' creativity and introducing local cultural arts at the primary education level.